Method for separating electrode material from current collectors of electrodes in used lithium-ion batteries

The method of exposing electrodes to high-pressure gases or supercritical fluids and rapid pressure reduction effectively separates electrode materials from current collectors, addressing inefficiencies in existing recycling methods and enabling high-purity recovery of valuable battery components.

JP2025511001APending Publication Date: 2025-04-15SOLVAY SPECIALTY POLYMERS ITALY SPA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024557581
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-01
Filing Date
2023-03-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Current methods for recycling electrode materials from spent batteries, particularly lithium-ion batteries, face challenges in efficiently separating the electrode material from the current collector without shredding, leading to impure and costly recovery processes with high environmental impact.

Method used

A method involving exposure of the electrode to a high-pressure gas or supercritical fluid, followed by rapid pressure reduction, which causes the electrode material to decompress and separate from the current collector, allowing for intact recovery of the current collector and pure electrode material.

Benefits of technology

Enables efficient and environmentally friendly separation of electrode materials from the current collector, facilitating high-purity recovery of valuable components like Li-based mixed oxides and salts, with minimal contamination and reuse potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511001000001
    Figure 2025511001000001
  • Figure 2025511001000002
    Figure 2025511001000002
  • Figure 2025511001000003
    Figure 2025511001000003
Patent Text Reader

Abstract

The present invention relates to a method for separating an electrode material from a current collector of a battery electrode, said method comprising the steps of: a- providing at least one electrode, said electrode comprising a current collector and a layer of electrode material adhered to said current collector, said layer of electrode material comprising an electroactive material in powder form and a binder; b- contacting said electrode with a gas or supercritical fluid at a pressure between (60) and 300 bar; and c- rapidly reducing the pressure of said gas or supercritical fluid by at least (60) bar within (30) seconds, thereby causing a rapid decompression of said gas.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to European patent application No. 22166304.0 (Nr 22166304.0), filed on April 1, 2022, the entire contents of which are incorporated herein by reference for all purposes.

[0002] The present invention relates to a method for separating an electrode material from a current collector of an electrode of a battery, typically a secondary battery, which method comprises exposing the electrode to a permeating gas at high pressure for a time sufficient for the gas to permeate the binder and pores of the electrode material, followed by a rapid release of the pressure, which allows the absorbed gas to rapidly decompress and completely separates the electrode material from the current collector. [Background technology]

[0003] The increasing use of rechargeable batteries (also known as "secondary batteries"), typically lithium-ion batteries, to power electrical and electronic devices, including electric vehicles, has created an increasing need to develop effective processes for recovering active materials from used batteries for reuse in new or refurbished batteries.

[0004] One of the key aspects that any battery recycling process must face before material recovery can truly begin is the separation of the battery into its constituent materials. The present invention is particularly directed to an improved method for separating the electrode material from the current collector.

[0005] As known to those skilled in the art, the electrodes of rechargeable batteries typically consist of a thin metal foil, called a "current collector," onto which a layer of electrode material is applied and adhered, for example, by casting, printing, or roll coating. This "electrode material" is a composition that mainly includes the powdered electroactive material (i.e., the component that actively participates in energy transfer) in powder form, and a binder, i.e., matrix, typically a thermoplastic matrix, that holds the active material together and provides the necessary adhesion to the current collector. The electrode material may include other optional components, such as materials that enhance electrical conductivity and / or control viscosity. Current commercially available batteries typically use graphite as the electroactive material in the anode and mixed oxides and salts containing lithium as the electroactive compound in the cathode. Since electrode materials, especially cathode materials, are traditionally the most valuable components recycled in batteries, a great deal of effort has been devoted to this area. Many processes that have been described and applied in practice to recover electroactive materials from spent batteries typically start with shredding the battery modules or electrodes into small pieces. This shredding process avoids the complications of disassembling the battery components. However, as Lei et al., "Lithium ion battery recycling using high-intensity ultrasonication," Green Chem., 2021, 23, 4710-4715, states, "...shredded components are difficult to separate into individual components with sufficient purity to form new battery materials. In recent years, it has been shown that separation of electrodes rather than shredding the batteries can significantly improve the purity of the resulting product and therefore the economics of the process."

[0006] The same document suggests that the use of ultrasound can help to break the adhesive bond between the electrode material and the current collector, allowing the current collector to be further recovered intact, however, such methods have not yet been fully developed industrially and there is still a continuing need to develop further methods for recovering electrode materials without shredding the batteries, used alone or in combination to achieve the most efficient and environmentally friendly recovery of electrode materials.

[0007] China Patent Application Publication No. 109103536, published on Dec. 28, 2018, describes a method for recycling active materials in lithium-ion batteries, in which the active materials are first removed from the current collector and then extracted with supercritical CO2. Summary of the Invention

[0008] The present invention relates to a method for separating an electrode material from a current collector of a battery electrode, the method comprising the steps of: a- providing at least one electrode, said electrode comprising a current collector and a layer of electrode material adhered to said current collector, said layer of electrode material comprising an electroactive material in powder form and a binder; b- contacting said electrode with a gas or a supercritical fluid at a pressure between 60 and 300 bar; c- Rapidly reducing the pressure of said gas or supercritical fluid by at least 60 bar within 30 seconds, thereby causing a rapid decompression of said gas. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The method of the present invention is a method for separating electrode material from the current collector of a battery electrode. Such a method is particularly useful when the battery is a rechargeable battery that has reached the end of its life, in other words a "spent" battery, i.e. a battery that cannot be charged any more and / or cannot provide a sufficient amount of energy for a sufficient time when charged. In particular, the method can be applied to electrodes recovered from spent lithium-ion batteries, which currently represent the majority of rechargeable batteries used worldwide, but also to future generations of batteries, as long as the electrode comprises a metal foil as a current collector, followed by a layer of electrode material that includes an electroactive component and a binder.

[0010] As mentioned in the "Background" section of this document, the most common process for recovering valuable materials from used batteries involves shredding the batteries into small pieces and then attempting to selectively dissolve or filter out the individual components using a combination of hydrometallurgical processes, but as can be read in the recent document "A critical review of current technologies for the liberation of electrode" (Science of the Total Environment 766(2021)142382-Elsevier BV), there are still many competing methods, each with their own advantages and disadvantages, and the biggest challenge lies in recovering materials pure enough to be reused in new batteries, with a low environmental impact and at a cost competitive with using new materials instead of the recovered materials. As can be seen from the cited documents, as of today, a "standard" method for recycling materials from used batteries has not yet been developed.

[0011] The method of the present invention is expected to make a useful contribution to one of the key parts of the recovery process, namely the separation of the current collector from the electrode material.

[0012] The first step of the method of the present invention is typically to provide at least one electrode from a used secondary battery. This can be easily achieved by mechanically disassembling the battery according to methods known in the art. A typical battery includes a battery case in which one or more battery cells are housed. An individual cell typically includes a positive electrode, a negative electrode, and a separator. The electrode is typically in the form of a rectangular sheet that is rolled or folded to form the cell. For example, the above-cited summary document (Science of the Total Environment 766(2021)142382-Elsevier BV) provides information on the common general knowledge in the art as far as mechanical disassembly of batteries is concerned.

[0013] The electrodes used in the present invention typically comprise a metal foil as a current collector that is coated with a layer of electrode material. The typical thickness of the current collector film is 5-30 micrometers, and the typical thickness of the coating of electrode material is 50-300 micrometers.

[0014] The nature of the metal foil used as the current collector depends on whether the electrode is a positive or negative electrode. When the electrode of the present invention is a positive electrode, the metal foil typically comprises, and preferably consists of, at least one metal selected from the group consisting of aluminum (Al), nickel (Ni), titanium (Ti), iron (Fe) and alloys thereof. A preferred current collector for the positive electrode is an Al foil. When the electrode of the present invention is a negative electrode, the metal foil typically comprises, and preferably consists of, at least one metal selected from the group consisting of silicon (Si), or lithium (Li), sodium (Na), zinc (Zn), magnesium (Mg), copper (Cu) and alloys thereof. A preferred current collector for the negative electrode is a Cu foil.

[0015] Electrode material compositions consist mostly of electroactive materials mixed with small amounts of binders, and optionally other components such as materials to enhance electrical conductivity (typically graphite).

[0016] When the electrode is a cathode or an anode, the electroactive material is different.

[0017] The electroactive material for the cathode is typically selected from metal oxides and salts containing Li, and typically these are mixed oxides and salts that also contain other metals such as Co, Mn, Ni, Fe, etc.

[0018] Preferably, the metal oxides and salts for the cathode material of the lithium-ion secondary battery can contain one or more lithium-containing compounds selected from the following: (i) Metal chalcogenides of the formula LiMQ2 (where M is at least one metal selected from transition metals, preferably from Co, Ni, Fe, Mn, Cr and V, and Q is a chalcogen preferably selected from those such as O or S). Among these, it is preferable to use lithium-based metal oxides of the formula LiMO2 (where M is the same as defined above). Particularly preferred examples thereof include LiCoO2, LiNiO2, LiNi x Co 1-x O2 (0 < x < 1) and spinel-structured LiMn2O4 may be mentioned. (ii) Compounds of the formula M1M2(JO4) f E 1-f (where M1 is lithium which may be partially substituted by one or more other alkali metals representing less than 20% of the M1 metal, M2 is a transition metal at an oxidation level of +2 selected from Fe, Mn, Ni or mixtures thereof which may be partially substituted by one or more additional metals representing less than 35% of the M2 metal, JO4 is any oxyanion where J is any of P, S, V, Si, Nb, Mo, or combinations thereof, E is a fluoride, hydroxide, or chloride anion, f is the mole fraction of the JO4 oxyanion, and is generally included in the range of 0.75 to 1) of lithiated or partially lithiated transition metal oxyanion-based electroactive materials. M1M2(JO4) as defined above f E 1-fThe electroactive material is preferably phosphate-based and may have an ordered or modified olivine structure. More preferably, the electroactive compound when forming the positive electrode has the formula Li 3-x M' y M'' 2-y (JO4)3, where 0≦x≦3 and 0≦y≦2, M′ and M″ are the same or different metals, at least one of which is a transition metal, and JO4 is preferably PO4 which may be partially substituted with another oxyanion, where J is any of S, V, Si, Nb, Mo or combinations thereof. Even more preferably, the electroactive material has the formula Li(Fe x Mn 1-x LiFePO4 is a phosphate-based electroactive material having the formula: LiFePO4, where 0≦x≦1, and x is preferably 1 (i.e., lithium iron phosphate of the formula LiFePO4). (iii) General formula (III) LiNi x M1 y M2 z Y2(III) (wherein M1 and M2 are the same or different and are transition metals selected from Co, Fe, Mn, Cr and V, and 0.5≦x≦1, in which case y+z=1−x, and Y preferably represents a chalcogen selected from O and S).

[0019] The electroactive material in this embodiment is preferably a compound of formula (III) in which Y is O. In a further preferred embodiment, M1 is Mn and M2 is Co or M1 is Co and M2 is Al. An example of such an active material is LiNi x Mn y Co z O2 (hereinafter referred to as NMC) and LiNi x Co y Al z O2 (hereinafter referred to as NCA). x Mn y Co zWith respect to O2, the content ratio of manganese, nickel, and cobalt can be varied to tune the power and energy performance of the battery.

[0020] In this embodiment of the invention, the electroactive material is preferably a compound of formula (III) as defined above, where 0.5≦x≦1, 0.1≦y≦0.5, and 0≦z≦0.5.

[0021] Non-limiting examples of suitable electroactive materials for the positive electrode of formula (III) include, in particular: LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.8 Co 0.2 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.9 Mn 0.05 Co 0.05 O2 Includes:

[0022] Among these, the compounds: LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNI 0,9 Mn 0,05 Co 0,05 O2 is particularly preferred.

[0023] The electroactive material for the anode typically comprises one or more carbon-based materials and / or one or more silicon-based materials. In some embodiments, the carbon-based material may be selected from graphite, such as natural or artificial graphite, graphene, or carbon black. These materials may be used alone or as a mixture of two or more thereof. The carbon-based material is preferably graphite.

[0024] The silicon-based compound may be one or more selected from the group consisting of chlorosilane, alkoxysilane, aminosilane, fluoroalkylsilane, silicon, silicon chloride, silicon carbide, and silicon oxide. More specifically, the silicon-based compound may be silicon oxide or silicon carbide.

[0025] When present in the electroactive material, the silicon based compound is included in an amount ranging from 1 to 60% by weight, preferably from 5 to 20% by weight, based on the total weight of the electroactive compound.

[0026] Another component of the electrode material is the binder, which is a key component of the electrode since it ensures good adhesion to the current collector and to the electroactive material, thus allowing the latter to transfer electrons as required.

[0027] Typically, the binder is a polymeric material. Suitable polymeric materials that can be used as binders are, for example, VDF-based polymers, SBR rubber, PAI polymers, sugar-based polymers (CMC, alginates, chitosan), polyacrylic acid, etc. In the present invention, the binder preferably comprises at least 50% by weight of one or more VDF-based polymers, since VDF-based polymers have optimal surface properties for the penetration of pressurized gas into the surface and pores, especially when using CO2 and supercritical CO2.

[0028] By "VDF-based polymer" is intended a polymer or copolymer that contains a majority of repeat units derived from 1,1,difluoroethylene (vinylidene fluoride, or VDF). VDF-based polymers suitable for use in the present invention contain at least 50 mol%, preferably at least 70 mol%, more preferably at least 80 mol%, and most preferably at least 90 mol% of repeat units derived from VDF. All percentages are based on the total amount of repeat units in the polymer.

[0029] The VDF polymers suitable as binders in the present invention preferably contain 0.1 to 10 mol %, more preferably 0.2 to 7.5 mol %, even more preferably 0.2 to 5 mol % of repeat units derived from the polymerization of ethylenically unsaturated monomers containing a polar group, preferably a carboxyl group. Examples of these non-fluorinated comonomers are especially hydrophilic (meth)acrylic monomers.

[0030] The hydrophilic (meth)acrylic monomer preferably has the formula: [ka] (In the formula, R1, R2, and R3 are equal to or different from each other and are independently a hydrogen atom or a C1-C3 hydrocarbon group, and R OHis hydrogen or a C1-C5 hydrocarbon moiety containing at least one hydroxyl group. Non-limiting examples of hydrophilic (meth)acrylic monomers are acrylic acid, methacrylic acid, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxyethylhexyl (meth)acrylate, among others.

[0031] The hydrophilic (meth)acrylic monomer is more preferably selected from: -Hydroxyethyl acrylate (HEA) of the formula: [ka] - 2-hydroxypropyl acrylate (HPA) of any of the following formulas: [ka] -Acrylic acid (AA) of the formula: [ka] - and mixtures thereof.

[0032] Most preferably, the hydrophilic (meth)acrylic monomer is AA and / or HEA.

[0033] Surprisingly, it has been found that electrode materials comprising binders comprising VDF polymers comprising polar comonomers as described above can then be more easily and efficiently recovered by the method of the present invention, even though, as is known in the art, such binders enhance adhesion to the current collector (see, for example, Solvay's WO2008129041A1).

[0034] Binders comprising the above VDF polymers are particularly suitable for use as binders in the cathode.

[0035] A typical composition of the electrode material includes 80% to 99% by weight of electroactive material, and 1% to 20% by weight of binder, based on the total weight of the electrode material.

[0036] In the second step of the process of the invention, at least one electrode provided in the first step must be exposed to a gas or supercritical fluid at high pressure. To do so, it is preferred that the electrode is fully unfolded and / or deployed in a flat configuration. If necessary, the electrode can be cut into smaller pieces, but one advantage of the method of the invention is that the entire electrode can be subjected to the method without the need to pre-cut the electrode.

[0037] The treatment at high pressure can be carried out in any suitable equipment. Typically, an autoclave is used. Multiple layers of electrodes can be stacked without adversely affecting the results of the method. Preferably, when multiple electrodes are treated simultaneously, the electrodes are of the same type, i.e., all anodes or all cathodes. It is further preferred to use the same electrode material for all electrodes exposed to high pressure simultaneously to minimize cross-contamination of electrode materials.

[0038] The choice of gas or supercritical fluid used in the present invention is not particularly important since the main effect of the gas or supercritical fluid is mechanical. In other words, the gas or supercritical fluid penetrates the pores of the electrode material, and when the pressure is released rapidly, the electrode material separates from the current collector. However, some preferred gases or supercritical fluids may be more effective in the separation process or require milder conditions and therefore perform better. The preferred gas or supercritical fluid may be preferably selected to have a certain affinity for the binder in terms of polarity and not react with any of the components of the electrode. The preferred chemical compounds that can be used for the gas or supercritical fluid in the method of the present invention have a critical density in the range of 0.470 to 0.220 g / ml. Examples of more preferred chemical compounds are, for example, CO2, H2O, CH3OH, CH3CH2OH, (CH3)2CO, N2O, and NH3. The use of NH3 and generally chemical compounds with basic properties, although effective in themselves, is not advisable when the binder comprises a VDF-based polymer, as it may adversely affect the binder. When the binder comprises a VDF-based polymer, the other chemical compounds in the list are preferred over NH3. One or more chemical compounds can be used to increase the pressure, but it is preferred to use one chemical compound. Generally, the autoclave is sealed with air at atmospheric pressure, and then one or more compounds are introduced to increase the pressure. In some embodiments, air can be removed from the autoclave before introducing one or more chemical compounds to increase the pressure. The treatment at high pressure is carried out at a pressure of 60 to 300 bar, preferably 90 to 270 bar, more preferably 100 to 250 bar. The temperature at which the treatment is carried out is not critical. Generally, it is preferred to operate at a temperature of 30 to 200 °C. Obviously, the temperature must be selected to allow the desired range of pressure to be increased with the selected gas or supercritical fluid, depending on the material used. For example, in the case of CO2, the appropriate temperature is 30 to 400°C, in the case of H2O, 100 to 700°C, in the case of CH3OH, 40 to 500°C, and in the case of CH3CH2OH, 50 to 600°C.

[0039] A preferred chemical compound for use in the present invention to increase pressure is CO2, and even more preferably supercritical CO2 (i.e., CO2 at a temperature and pressure that is in the supercritical state according to the CO2 phase diagram).

[0040] In a preferred embodiment of the process of the present invention, the electrodes are contacted with a co-solvent before sealing the autoclave. This step has been found to facilitate the separation process. Without being bound by theory, it is believed that wetting the electrode material with the co-solvent facilitates the penetration of the gas or supercritical fluid into the pores of the material, especially into the pores of the junction between the electrode material and the current collector. Suitable co-solvents are water or weakly acidic aqueous solutions, alcohols, liquid CO2, linear or cyclic esters, polar aprotic solvents such as N-methylpyrrolidone, dimethylsulfoxide, γ-valerolactone, γ-butyrolactone, diesters such as Rhodiasolv® RPDE. When CO2 is used, it can be introduced into the autoclave in solid form for ease of handling, since it may change to a liquid and then to a gas / supercritical fluid state when carrying out the process at the conditions selected for high pressure processing. After the autoclave or other pressure-resistant device is sealed, the temperature is increased to the desired level and the pressure is typically increased through an inlet. Alternatively, in combination with an inlet that can be used to more precisely control the pressure, a co-solvent can be selected and introduced into the autoclave in an amount such that, upon reaching a selected temperature, the co-solvent is converted to a gas or supercritical fluid, thus increasing the desired pressure within the system.

[0041] Surprisingly, it has been found that the exposure time to the selected temperature and pressure can be very short, because simply exposing the electrode to high pressure causes the gas or supercritical fluid to penetrate the pores almost instantly. Longer exposure times for the selected conditions are advantageous in that they ensure more complete penetration of the gas or supercritical fluid into the pores of the electrode material and are adsorbed onto the binder surface, but as the exposure time increases, the benefits of longer exposure times tend to become less and less, so preferably, the exposure time can vary widely from 0.1 seconds to 24 hours, but more preferably, for process economy, the exposure time is between 0.1 seconds and 60 minutes.

[0042] The third step of the method of the present invention is to rapidly reduce the pressure set in the previous step. Rapidly reducing the pressure in the system causes the gas (or supercritical fluid) to expand rapidly, which causes the electrode material to separate from the current collector foil.

[0043] Without being bound by theory, it is believed that the gas or supercritical fluid can penetrate the pores of the electrode material and be adsorbed on the surface by the polymer binder.

[0044] When pressure in the system is suddenly released, the gas or supercritical fluid expands very rapidly before it can migrate out of the pores, causing the electrode material coating to change size and shape. This change in size and shape can result in a complete loss of adhesion between the electrode material and the current collector. The current collector film can typically be recovered intact, but the electrode material may be collected in pieces and / or brushed off the surface of the current collector.

[0045] As mentioned above, to obtain the desired effect, the pressure release must be very rapid, so a drop of at least 60 bar is required within 30 seconds. However, as a general rule, the faster and larger the pressure drop, the more effective the process is. Thus, it is preferred that the process has a pressure drop of at least 90 bar within 30 seconds, even more preferred within 20 seconds, and even more preferred within 10 seconds. In one embodiment, the pressure is released from the maximum processing pressure to ambient pressure in less than 30 seconds, preferably less than 20 seconds, and more preferably less than 10 seconds.

[0046] The process of the present invention is particularly advantageous because the current collector foil can be recovered in its entirety and reused as such, whereas the electrode material can be recovered separately and treated according to one of the known methods to separate the electroactive material from the binder (e.g., using a solvent in the binder). One advantage of the process of the present invention is that there is virtually no contamination of the electrode material by the current collector. The process is environmentally friendly, since the gases or supercritical fluids used can be completely recovered and reused.

[0047] The process of the present invention is particularly useful for cathode recovery since the cathode electroactive material (Li-based mixed oxides and salts) is the most valuable component of the battery and requires high purity, making its recycling of the greatest economic and environmental importance.

[0048] To the extent that the disclosures of any patents, patent applications, and publications incorporated herein by reference conflict with the statements in this application to the extent that any term may be unclear, the statements in this application shall control. EXAMPLES

[0049] Example 1 Al foil as the current collector, and PVDF / AA binder (Solef® 5130) and LiNi as the electroactive material. 0.8 Mn 0.1 Co 0.1Three flat cathodes (each with dimensions 4 × 0.5 cm) containing the cathode material with O2 were placed in a stainless steel autoclave with a volume of 100 mL. 14 g of solid CO2 were added dispersed on top of the cathodes. The autoclave was then closed and heated to 100 °C. The pressure of the CO2 was measured to be 95 bar and adjusted to 100 bar using the CO2 inlet. The selected pressure and temperature were maintained for 15 minutes, then the autoclave outlet was opened to rapidly reduce the pressure to normal pressure in 5 seconds. The cathode material was found to be completely peeled off from the Al foil and could be fully recovered. The Al foil was not damaged.

[0050] Example 2 The same process as in Example 1 was used, but with three flat anodes of the same size (Cu current collector, and anode material graphite / silicon oxide with SBR binder). It was found that the anode material was completely peeled off from the Cu foil. The Cu foil was not damaged.

Claims

1. a- providing at least one electrode, said electrode comprising a current collector and a layer of electrode material adhered to said current collector, said layer of electrode material comprising an electroactive material in powder form and a binder; b- contacting said electrode with a gas or supercritical fluid at a pressure between 60 and 300 bar; c- rapidly reducing the pressure of the gas or supercritical fluid by at least 60 bar within 30 seconds, thereby causing a rapid decompression of the gas.

2. The method according to claim 1, wherein in step b, the electrodes are subjected to a pressure of between 90 and 270 bar, preferably between 100 and 250 bar.

3. 3. The method of claim 1 or 2, wherein in step c the pressure is rapidly reduced by at least 90 bar within 30 seconds, or by at least 90 bar within 20 seconds, or by at least 90 bar within 10 seconds.

4. A method according to any one of claims 1 to 3, wherein in step c) the pressure is rapidly reduced from maximum processing pressure to ambient pressure in less than 30 seconds, preferably less than 20 seconds, more preferably less than 10 seconds.

5. The method of any one of claims 1 to 4, wherein the at least one electrode is a cathode.

6. The method of any one of claims 1 to 5, wherein the electroactive material comprises metal oxides and salts containing Li.

7. 7. The method of claim 1, wherein the electrode material comprises 80% to 99% by weight of electroactive material and 1% to 20% by weight of a binder, based on the total weight of the electrode material.

8. The method according to any one of the preceding claims, wherein the binder comprises, preferably consists of, one or more VDF type polymers.

9. The VDF-based polymer comprises at least 50 mol %, preferably at least 70 mol %, more preferably at least 80 mol %, and most preferably at least 90 mol % of repeat units derived from VDF and 0.1 to 10 mol %, more preferably 0.2 to 7.5 mol %, and even more preferably 0.2 to 5 mol % of repeat units of the formula: 【Chemistry 1】 (wherein R1, R2, and R3 are equal to or different from each other and independently represent a hydrogen atom or a C 1 ~C 3 is a hydrocarbon group, and R OH is hydrogen or a C containing at least one hydroxyl group 1 ~C 5 and a repeat unit derived from a (meth)acrylic monomer, the repeat unit being a hydrocarbon moiety.

10. 10. The method of claim 9, wherein the (meth)acrylic monomer is selected from acrylic acid, hydroxyethyl acrylate, hydroxypropyl acrylate, and mixtures thereof.

11. A method according to any one of the preceding claims, wherein the gas or supercritical fluid has a critical density in the range of 0.470 to 0.220 g / ml.

12. The gas or supercritical fluid is CO 2 , H 2 O, C.H. 3 OH, CH 3 CH 2 OH, (CH 3 ) 2 CO, preferably supercritical CO 2 The method according to any one of claims 1 to 11, wherein